Effect of Changes in Working Capital and Current Ratio on Return on Equity at PT. Kalbe Farma Tbk. Period 2010 – 2020 - Oktaviyanti, Asmi; Sairin, Sairin (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This research aims to determine the influence of changes in working capital and current ratio on return on equity at PT. Kalbe Farma Tbk for the 2010 – 2020 period, both partially and simultaneously. This research method uses a quantitative descriptive method, namely conducting research that describes the company's financial condition expressed in numerical form. The type of data used in research is secondary data. The type of secondary data used is the financial report of PT. Kalbe Farma Tbk for the period 2010 – 2020 within a period of 11 years. Obtained from BEI (Indonesian Stock Exchange) and PT website. Kalbe Farma Tbk. The analytical methods used in this research are descriptive statistical tests, classical assumption tests, simple linear regression tests, multiple linear regression, correlation coefficient tests, coefficient of determination tests, and hypothesis tests. The research results show that partial changes in working capital (X1) do not have a significant effect on return on equity (Y) with t calculated at 1.536 < t table 2.306. With a significant level of 0.163 > 0.05. Partially the current ratio (X2) has a significant effect on return on equity (Y) with a calculated t of 2.372 > t table 2.306. With a significant level of 0.026 <0.05. Simultaneously there is a significant positive influence of changes in working capital (X1) and current ratio (X2) on return on equity (Y) with a calculated f value of 4.560 > f table 4.46 with a significance level of 0.048 < 0.05.